STRATEGI PENGEMBANGAN PARIWISATA BERBASIS MASYARAKAT DI DESA KEMETUL, KABUPATEN SEMARANG - Rindo Bagus Sanjaya (Magister Tourism Study, Faculty of Tourism, Udayana University, 2018)
This research aims to determine the potential of tourism based on supporting and inhibiting factors of rural tourism development in Desa Kemetul and analyzing the strategy of community-based tourism in Desa Kemetul. The research was conducted in Desa Kemetul Kecamatan Susukan Kabupaten Semarang. This study uses qualitative method which the data obtained through depth interviews with Kepala Desa Kemetul, Chairman of POKDARWIS Sekar Kanthil, Local Communities, and Dinas Pariwisata Kabupaten Semarang, and then the data were analyzed using SWOT analysis. The study concluded that Desa Kemetul has a lot of tourism potential to become tourist attraction. Desa Kemetul needs to consider strengthening flagship product, the strategy of sustainable development of a tourist attraction, and strategies for institutional development and human resources.